Thermal valorization of sewer sludge: Perspectives for large wastewater treatment plants. (20th November 2016) - Panepinto, Deborah; Fiore, Silvia; Genon, Giuseppe; Acri, Marco
Abstract: The smart identification of a proper solution for the final destination of sewer sludge generated by wastewater treatment is currently a strategic and compelling topic. Sludge quantity conspicuously increased in the last years, and it may be considered without any doubt as a very interesting substrate for energetic valorization processes. Therefore the investigation of sludge incineration through the here proposed methodology applied to a significant case study, such as a WWTP treating 2.7 M p.e. organic load, maybe useful for EU highly populated contexts operating centralized urban water systems. In fact, although anaerobic digestion and composting are still the most commonly adopted solutions for sludge management even in large WWTPs, the introduction of a sludge-to-energy approach will be mandatory in the next future. The first step of the implemented approach consisted in a baseline analysis, which was necessary to define the main qualitative and quantitative characteristics of the sludge. Afterwards a detailed hypothesis about a potential plant configuration was formulated, considering its feasibility from the technological and economic point of view and the environmental drawbacks as well. The proposed methodology was validated taking into account the sludge deriving from the largest Italian WWTP (inflow 200, 000, 000 m 3 /y of civil and industrial wastewater). The amount of generated sludge is approximately 100, 000 t/y (38.9% DS) and after anaerobic digestion it is destined to centrifugation, filtration and thermal drying. The circumstance that the mentioned processes are performed on a full-scale, together with an extended characterization of the generated outflows, allowed a sound investigation of the effect of pre-treatments on thermal valorization of the sludge. An economic evaluation of the incineration proposal showed that the final cost of the sludge disposal would be of about 63–65 Euro/t for the considered case study.